Antimicrobial agent, resin composition, and method for producing the antibacterial agent
Patent Information
- Application Number
- JP2024011190
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2024-01-29
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2044-01-29
AI Technical Summary
【0017】 本発明に係る抗菌剤によれば、抗菌性が長く継続する徐放性の抗菌剤を提供することができる。
Smart Images

Figure 2025029557000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an antibacterial agent, a resin composition, and a method for producing the antibacterial agent. [Background technology]
[0002] In recent years, due to the prevalence of viral infections, there is an increasing need for antibacterial agents and products with antibacterial properties against bacteria and viruses. Plastic products (resin products) are desired as antibacterial products due to their high functionality (durability, lightness, ease of processing) and cost advantage.
[0003] On the other hand, there is a desire to reduce the amount of plastic used in plastic products due to the problem of marine plastic waste and the realization of a recycling-oriented society. In addition, in recent years, there has been an increasing demand for the 3Rs, namely reduce, reuse, and recycle.
[0004] From the perspective of the above-mentioned antibacterial properties, reducing the amount of plastic used, and the 3Rs, antibacterial agents made from eggshells, which are usually discarded, and the use of plastic products containing these antibacterial agents are being considered.
[0005] Patent Document 1 discloses a method for producing a biodegradable resin composition containing eggshell powder including digested powder of baked eggshells and a biodegradable resin powder, the method including the production of the biodegradable resin composition containing eggshell powder in a ratio of 1% by mass to 80% by mass. According to Patent Document 1, the digested powder is a baked product mainly composed of calcium hydroxide obtained by hydration (digestion). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6802242 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the resin composition of Patent Document 1, the extinguishing powder is mainly composed of calcium hydroxide, so that the entire exposed surface of the eggshell powder exposed on the surface of the resin composition comes into contact with moisture in the air and begins to dissolve quickly. Although the solubility of calcium hydroxide is relatively small, if the dissolution of the eggshell powder continues, the eggshell powder on the exposed surface may be quickly depleted, causing the antibacterial properties to disappear, or the exposed surface of the eggshell powder may become strongly alkaline, causing rough skin on the user's contact area.
[0008] Thus, the resin composition of Patent Document 1 has a problem in that the antibacterial properties of the eggshell powder exposed on the surface of the resin composition may quickly disappear. It is also presumed that the antibacterial properties may quickly disappear when the eggshell powder used in Patent Document 1 is itself used as an antibacterial agent.
[0009] The present invention is devised to solve the above problems, and has an object to provide a sustained-release antibacterial agent having long-lasting antibacterial activity, a method for producing the same, and a resin composition and a resin molded article containing the antibacterial agent. [Means for solving the problem]
[0010] The antibacterial agent according to the present invention comprises calcium oxide particles containing calcium oxide and a hydration-inhibiting component that inhibits hydration of the calcium oxide, The pH of the surface of the calcium oxide particles is 12.0 or higher.
[0011] The hydration inhibitor is preferably magnesium oxide.
[0012] The calcium oxide particles preferably have a dispersed phase made of magnesium oxide dispersed in a matrix phase made of calcium oxide.
[0013] The calcium oxide particles are preferably baked eggshell particles.
[0014] The resin composition according to the present invention contains the antibacterial agent and a resin.
[0015] The resin molded article according to the present invention contains the resin composition.
[0016] The method for producing an antibacterial agent according to the present invention includes a calcination step of calcining dried eggshells at 1000°C or higher for 1 to 2 hours to obtain calcium oxide particles containing calcium oxide and a hydration-inhibiting component that inhibits hydration of the calcium oxide, and having a surface pH of 12.0 or higher. Effect of the Invention
[0017] According to the antibacterial agent of the present invention, it is possible to provide a sustained-release antibacterial agent whose antibacterial activity lasts for a long period of time.
[0018] According to the method for producing an antibacterial agent of the present invention, it is possible to efficiently produce a sustained-release antibacterial agent whose antibacterial activity lasts for a long time.
[0019] According to the resin composition of the present invention, the surface and the inside of the resin composition and a resin molded article molded using the resin composition have antibacterial properties.
[0020] According to the resin molded article of the present invention, the surface and the inside of the resin molded article have antibacterial properties. [Brief description of the drawings]
[0021] [Figure 1] 1 is an example of a scanning electron microscope (SEM) photograph of calcium oxide particles 20 contained in the antibacterial agent according to the present invention, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). [Diagram 2] This is an example of the results of a qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100A (100) (sample A) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Small black dots of about 1 μm in size indicate pores, dark gray areas indicate the distribution of Ca, and light gray areas indicate the distribution of Mg. [Diagram 3] Figure 2 shows an example of the qualitative analysis results, showing only the distribution of Ca. The small black dots, each about 1 μm in size, are pores, and the relatively white areas are areas showing only the distribution of Ca. [Figure 4] Figure 2 shows an example of the qualitative analysis results, showing only the distribution of Mg. The small black dots of about 1 μm in size are pores, and the relatively white areas are areas showing only the distribution of Mg. [Diagram 5] This is an example of the results of a qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of dried eggshell 100B(100) (sample B) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Small black dots of about 1 μm in size indicate pores, dark gray areas indicate the distribution of Ca, and light gray areas indicate the distribution of Mg. [Figure 6] This is an example of the results of a qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of dried eggshell 100C(100) (sample C) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Small black dots of about 1 μm in size indicate pores, dark gray areas indicate the distribution of Ca, and light gray areas indicate the distribution of Mg. [Figure 7] This is an example of the results of a qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of dried eggshell 100D(100) (sample D) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Small black dots of about 1 μm in size indicate pores, dark gray areas indicate the distribution of Ca, and light gray areas indicate the distribution of Mg. [Figure 8] This is an example of the results of a qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100E (100) (sample E) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Small black dots of about 1 μm in size indicate pores, dark gray areas indicate the distribution of Ca, and light gray areas indicate the distribution of Mg. [Figure 9]FIG. 1 is a diagram showing the pH range of calcium oxide particles 20 contained in the antibacterial agent according to the present invention, the pH range in which various bacteria can survive, and the pH range in which various viruses are not inactivated. [Figure 10] FIG. 1 is a diagram showing an example of a method for producing an antibacterial agent according to the present invention. [Figure 11] FIG. 1 is a diagram showing an example of application of the antibacterial agent according to the present invention. [Figure 12] 1 is an example of a scanning electron microscope (SEM) photograph of the surface of test piece No. A3 of Example 2, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). [Figure 13] Figure 12 shows an example of the qualitative analysis results showing only the distribution of Ca. In the figure, the relatively white parts show only the distribution of Ca. [Figure 14] Figure 12 shows an example of the qualitative analysis results showing only the distribution of Mg. In the figure, the relatively white parts show only the distribution of Mg. [Figure 15] Figure 12 is an example of the qualitative analysis results shown only in the distribution of O. In the figure, the relatively white parts are the parts shown only in the distribution of O. [Figure 16] 1 is an example of a scanning electron microscope (SEM) photograph of another surface of test piece No. A3 of Example 2, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). [Figure 17] Figure 16 shows an example of the qualitative analysis results showing only the distribution of Ca. In the figure, the relatively white parts show only the distribution of Ca. [Figure 18] Figure 16 shows an example of the qualitative analysis results shown only in terms of the distribution of Mg. In the figure, the relatively white areas show only the distribution of Mg. [Figure 19] Figure 16 is an example of the qualitative analysis results shown only in the distribution of O. In the figure, the relatively white parts are the parts shown only in the distribution of O. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The antibacterial agent will be described below.
[0023] [Antibacterial agents] The antibacterial agent according to the present invention contains calcium oxide particles. The antibacterial agent according to the present invention is generally made of calcium oxide powder, which is an aggregate of fine calcium oxide particles.
[0024] (Calcium oxide particles) Each of the calcium oxide particles contains calcium oxide and a hydration-inhibiting component that inhibits the hydration of the calcium oxide.
[0025] The hydration inhibitor may be, for example, magnesium oxide. Therefore, the calcium oxide particles contain, for example, calcium oxide and magnesium oxide. Magnesium oxide is sparingly soluble.
[0026] When the calcium oxide particles contain calcium oxide and magnesium oxide, the calcium oxide particles usually have a dispersed phase made of magnesium oxide dispersed in a matrix phase made of calcium oxide.
[0027] Fig. 1 is an example of a scanning electron microscope (SEM) photograph of calcium oxide particles 20 contained in the antibacterial agent according to the present invention, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). The calcium oxide particles 20 shown in Fig. 1 have a long-short average diameter, which is the arithmetic mean value of the long diameter and the short diameter, of about 10 to 15 µm. In Fig. 1, a plurality of calcium oxide particles 20 are aggregated to form calcium oxide powder.
[0028] FIG. 2 is an example of a qualitative analysis result of the surface of a dried eggshell 100A (100) (sample A) before firing, which is a raw material of calcium oxide particles 20 contained in the antibacterial agent according to the present invention, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). Sample A is an example of a white eggshell of a chicken. In FIG. 2, small black dots of about 1 μm in size indicate pores, dark gray areas indicate Ca distribution, and light gray areas indicate Mg distribution. FIG. 3 is an example of a qualitative analysis result showing FIG. 2 only with Ca distribution. Small black dots of about 1 μm in size indicate pores, and relatively white areas indicate only Ca distribution. FIG. 4 is an example of a qualitative analysis result showing FIG. 2 only with Mg distribution. Small black dots of about 1 μm in size indicate pores, and relatively white areas indicate only Mg distribution.
[0029] In Figure 2, when the figure is divided into 2 equal parts vertically and horizontally, the dark gray area showing Ca distribution is relatively abundant in the upper right part. However, in Figure 2, the light gray dispersed phase showing Mg distribution is relatively uniformly dispersed in the dark gray matrix phase showing Ca distribution.
[0030] That is, as shown in FIG. 2, the surface of the baked eggshell 100A (sample A) is such that a dispersed phase made of magnesium oxide is dispersed relatively uniformly in a matrix phase made of calcium oxide.
[0031] The distribution of Ca and Mg in an unsintered eggshell does not usually change significantly from that in a fired eggshell. Therefore, the calcium oxide particles 20 obtained by firing the fired eggshell 100A (sample A) shown in Figures 2 to 4 have a dispersed phase of magnesium oxide dispersed relatively uniformly in a matrix phase of calcium oxide, similar to those shown in Figures 2 to 4.
[0032] As shown in FIG. 2, calcium oxide particles 20 are preferably such that a dispersed phase made of magnesium oxide is dispersed relatively uniformly in a matrix phase made of calcium oxide, since this inhibits hydration of calcium oxide in calcium oxide particles 20 and makes it easier for the antibacterial action of calcium oxide particles 20 to last for a long period of time.
[0033] As the calcium oxide particles 20, for example, baked eggshell particles are used. Here, the baked eggshell particles are particles of baked eggshell, and the baked eggshell is a baked eggshell. The baked eggshell has a structure in which a dispersed phase made of magnesium oxide is dispersed relatively uniformly in a matrix phase made of calcium oxide, and it is preferable because it is easy to obtain baked eggshell particles in which the dispersed phase is dispersed relatively uniformly in the matrix phase. In addition, the eggshell has a relatively coarse structure with many pores in the surface direction, rather than a dense structure like a shell, in order to allow air to pass through the inside and outside of the eggshell. For this reason, the baked eggshell is preferable because it can be easily broken down by only baking or by a weak loosening operation to obtain baked eggshell particles, and therefore can be manufactured with less equipment and less energy.
[0034] The baked eggshell is preferably one obtained by baking eggshells that do not contain egg membrane, since the bad odor derived from the protein in the egg membrane is less likely to remain in the baked eggshell particles or to contaminate the inside of the baking equipment.
[0035] Examples of eggshells that can be used include chicken eggs, quail eggs, and ostrich eggs. Among these, chicken eggs are preferred because the eggshell tends to have a dispersed phase of magnesium oxide dispersed relatively uniformly in a matrix phase of calcium oxide. Meanwhile, the eggshell of quail eggs tends to have a dispersed phase of magnesium oxide dispersed non-uniformly in a matrix phase of calcium oxide, for example, large dispersed phases are unevenly distributed in the matrix phase.
[0036] Fig. 5 shows an example of the results of qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100B (100) (sample B) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Sample B is an example of a quail eggshell. In Fig. 5, the cracked areas indicate cracks in the eggshell, the small black dots about 1 µm in size indicate pores, the dark grey areas indicate the distribution of Ca, and the light grey areas indicate the distribution of Mg.
[0037] In Figure 5, there are light gray areas indicating the distribution of Mg in the long horizontal section above the crack that runs parallel to the crack from the center of the left side to the upper right side, and in the wide C-shaped section below the crack. In Figure 5, the rest of the area other than the light gray areas is mostly dark gray, indicating the distribution of Ca. In Figure 5, the dispersed phase of magnesium oxide is locally arranged in the matrix phase of calcium oxide, and the dispersed phase is unevenly distributed.
[0038] As shown in FIG. 5, if the calcium oxide particles 20 have a dispersed phase of magnesium oxide unevenly distributed in the matrix phase of calcium oxide, the hydration of calcium oxide in the calcium oxide particles 20 is difficult to suppress, and the antibacterial effect of the calcium oxide particles 20 may not be sustained for a long period of time.
[0039] Fig. 6 shows an example of the results of qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100C (100) (sample C) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Sample C is an example of a red chicken eggshell. In Fig. 6, small black dots with a size of about 1 µm indicate pores, dark grey areas indicate the distribution of Ca, and light grey areas indicate the distribution of Mg.
[0040] In FIG. 6, the light gray dispersed phase indicating the distribution of Mg is dispersed fairly uniformly in the dark gray matrix phase indicating the distribution of Ca.
[0041] Fig. 7 shows an example of the results of qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100D (100) (sample D) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Sample D is another example of a red chicken eggshell. In Fig. 7, small black dots with a size of about 1 µm indicate pores, dark grey areas indicate the distribution of Ca, and light grey areas indicate the distribution of Mg.
[0042] In FIG. 7, the light gray dispersed phase indicating the distribution of Mg is dispersed fairly uniformly in the dark gray matrix phase indicating the distribution of Ca.
[0043] Fig. 8 shows an example of the results of qualitative analysis, by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), of the surface of a dried eggshell 100E (100) (sample E) before firing, which is the raw material for calcium oxide particles 20 contained in the antibacterial agent according to the present invention. Sample E is another example of a white chicken eggshell. In Fig. 8, small black dots with a size of about 1 µm indicate pores, dark grey areas indicate the distribution of Ca, and light grey areas indicate the distribution of Mg.
[0044] In Figure 8, the dark gray area showing Ca distribution is relatively abundant from the center to the left side of the figure, and the light gray area showing Mg distribution is somewhat concentrated in the lower part of the center and the lower right part. However, in Figure 8, the light gray dispersed phase showing Mg distribution is relatively uniformly dispersed in the dark gray matrix phase showing Ca distribution as a whole.
[0045] That is, as shown in FIG. 8, the surface of the baked eggshell 100E (sample E) is such that a dispersed phase made of magnesium oxide is dispersed relatively uniformly in a matrix phase made of calcium oxide.
[0046] The calcium oxide particles 20 contain 0.5 to 10 mass %, preferably 1 to 5 mass %, of magnesium oxide. When the magnesium oxide content is within the above range, hydration of calcium oxide in the calcium oxide particles 20 is suppressed, and the antibacterial effect of the calcium oxide particles 20 tends to last for a long period of time, which is preferable.
[0047] The size of the calcium oxide particles 20 is, for example, 1 μm or more and 20 μm or less. If the size of the calcium oxide particles 20 is within the above range, it is preferable because the calcium oxide particles 20 tend to contain sufficient calcium oxide and magnesium oxide. Here, the "size of the calcium oxide particles 20" means the maximum length of the particles.
[0048] It is preferable that the calcium oxide particles 20 have a long and short average diameter of 10 to 15 μm, because the calcium oxide particles 20 are easily uniformly dispersed in a resin composition obtained by mixing a calcium oxide powder, which is an aggregate of the calcium oxide particles 20, with a resin, and the calcium oxide particles 20 are easily exposed on the surface of the resin composition. The long and short average diameter is the arithmetic mean value of the long diameter and the short diameter.
[0049] It is preferable that the calcium oxide particles 20 have an average major axis diameter of 1 to 3 μm, because when calcium oxide powder, which is an aggregate of the calcium oxide particles 20, is incorporated into fibers, the calcium oxide particles 20 are easily exposed on the surface of the fibers.
[0050] The pH of the surface of the calcium oxide particles 20 is 12.0 or more, preferably 12.2 or more. Here, the pH of the calcium oxide particles 20 means the pH in equilibrium with the water when the surface of the calcium oxide particles 20 is brought into contact with the water.
[0051] The calcium oxide particles 20 according to the present invention contain calcium oxide and a hydration-inhibiting component such as magnesium oxide that inhibits the hydration of calcium oxide, and preferably have a dispersed phase made of magnesium oxide dispersed in a matrix phase made of calcium oxide.
[0052] Therefore, when calcium oxide particles 20 according to the present invention come into contact with moisture, the exposed calcium oxide portion quickly produces calcium hydroxide and dissolves in moisture, resulting in a localized pH of 12.0 or higher. On the other hand, the hydration inhibitor component such as magnesium oxide in calcium oxide particles 20 according to the present invention is generally poorly soluble, and inhibits the contact of calcium oxide portions with moisture and inhibits the production of calcium hydroxide. Therefore, when calcium oxide particles 20 according to the present invention come into contact with moisture, the change from calcium oxide to calcium hydroxide and the dissolution of calcium hydroxide proceed relatively slowly overall.
[0053] The pH of the particle surface of the calcium oxide particles 20 is the pH in an equilibrium state of the moisture when the moisture is brought into contact with the surface of the calcium oxide particles 20, and is therefore the pH of the entire moisture in contact with the particle surface of the calcium oxide particles 20. The antibacterial agent according to the present invention usually has a particle surface pH of 12.0 or more, similar to the calcium oxide particles 20.
[0054] FIG. 9 is a diagram showing the pH range of the calcium oxide particles 20 contained in the antibacterial agent according to the present invention, the pH range in which various bacteria can survive, and the pH range in which various viruses are not inactivated. In FIG. 9, the rectangular area indicated as VOBLEED is the pH range of the antibacterial agent according to the present invention (the antibacterial agent is composed only of the calcium oxide particles 20). In FIG. 9, the horizontally elongated bands with the name of the bacteria or virus and numerical values on the left and right indicate the lower and upper limits of pH at which the bacteria or virus is not alive or inactive. For example, "6 Foot-and-mouth disease virus 9" indicates that the foot-and-mouth disease virus is not inactive within the range of pH 6 to 9, and is inactive at a pH below 6 and above pH 9. Also, "4 Salmonella 9" indicates that the Salmonella bacteria survives within the range of pH 4 to 9, and is inactive at a pH below 4 and above pH 9.
[0055] As shown in Fig. 9, general bacteria and viruses are killed or inactivated at a pH of more than 12.6. In the antibacterial agent according to the present invention, the pH of the particle surface of the calcium oxide particles 20 is 12.0 or more, so that general bacteria and viruses that come into contact with the calcium oxide particles 20 of the antibacterial agent are killed or inactivated.
[0056] The calcium oxide particles 20 are white, with a whiteness of 90 to 100. Here, the whiteness is an index obtained by dividing the whiteness of a surface to which extremely fine magnesium oxide powder is attached into 100 and a dark state into 0, and dividing the whiteness into 100 equal parts. The antibacterial agent according to the present invention usually has a whiteness of 90 to 100, similar to the calcium oxide particles 20, and is white.
[0057] It is preferable that the whiteness of the calcium oxide particles 20 or the antibacterial agent is within the above range, since the color of the resin composition containing the antibacterial agent and a resin, or the resin molded body containing the resin composition, can be made to have a wide variety of colors, including white.
[0058] (action) According to the antibacterial agent of the present invention, the calcium oxide particles 20 constituting the antibacterial agent have antibacterial properties, and the antibacterial properties show a sustained release property that continues for a long time. The antibacterial properties of the calcium oxide particles 20 are due to the fact that the exposed part of calcium oxide contained in the calcium oxide particles 20 reacts with moisture in the air or the like to generate calcium hydroxide, and this calcium hydroxide dissolves in moisture, making the surface of the calcium oxide particles 20 strongly alkaline at pH 12.0 or more. The reason why the antibacterial properties of the antibacterial agent are sustained release is because the magnesium oxide contained in the calcium oxide particles 20 is poorly soluble in water, and therefore the calcium oxide particles 20 as a whole undergo a relatively slow change from calcium oxide to calcium hydroxide and dissolution of calcium hydroxide. According to the antibacterial agent of the present invention, the surface and inside of the resin composition and resin molded body obtained by mixing the antibacterial agent with a resin have sustained release antibacterial properties.
[0059] (effect) According to the antibacterial agent of the present invention, a sustained-release antibacterial agent whose antibacterial activity lasts for a long period of time can be obtained.
[0060] Furthermore, when the calcium oxide particles 20 constituting the antibacterial agent according to the present invention are baked eggshell particles, the calcium oxide particles 20 are formed from natural materials, so that an environmentally friendly antibacterial agent can be obtained.
[0061] [Method of manufacturing antibacterial agent] The method for producing an antibacterial agent according to the present invention includes a firing step.
[0062] Fig. 10 is a diagram showing an example of a method for producing an antibacterial agent according to the present invention. In the example of the method for producing an antibacterial agent shown in Fig. 10, eggshells are used as a raw material to produce calcium oxide powder (calcined eggshell powder) which is an aggregate of calcium oxide particles 20 containing calcium oxide and a hydration-inhibiting component that inhibits the hydration of the calcium oxide and having a surface pH of 12.0 or higher. The method for producing an antibacterial agent according to the present invention may include a drying step before the calcination step S20, or may include a grinding step at least either before or after the calcination step S20, as necessary.
[0063] (drying process) When eggshells are used as the raw material, the drying step is a step of drying the eggshells to obtain dried eggshells 100. It is preferable that the eggshells before drying do not contain egg membranes. If the eggshells before drying do not contain egg membranes, it is preferable that the baked eggshells obtained in the baking step S20 do not have a protein-derived odor. The drying temperature in the drying step is preferably 90 to 120°C.
[0064] (Firing process) The firing step S20 is a step of firing the dried eggshells 100 at 1000°C or higher for 1 to 2 hours to obtain calcium oxide particles 20 that contain calcium oxide and a hydration-inhibiting component that inhibits the hydration of the calcium oxide, and have a surface pH of 12.0 or higher. When the dried eggshells 100 are used as the raw material, the calcium oxide particles 20 obtained in the firing step S20 usually take the form of calcium oxide powder that is an aggregate of the calcium oxide particles 20 (fired eggshell powder that is an aggregate of fired eggshell particles).
[0065] The baking step S20 is performed, for example, by baking the dried eggshells 100 in a baking furnace such as a continuous furnace. Note that Fig. 10 shows an example of the baking step S20, in which the dried eggshells 100 contained in a cylindrical container are baked in a continuous furnace. However, the baking furnace and the container for holding the dried eggshells 100 used in the baking step S20 of the present invention are not limited to those shown in Fig. 10. Moreover, the baking step S20 of the present invention may be performed by directly placing the dried eggshells 100 on a conveyor or the like in the baking furnace, without using a container for holding the dried eggshells 100.
[0066] The firing temperature in the firing step S20 is preferably 1100° C. or higher, and more preferably 1200° C. or higher.
[0067] The firing time at the above firing temperature in the firing step S20 is preferably 1 to 2 hours.
[0068] (Crushing process after the firing process) The pulverization step S30 following the firing step S20 is a step in which the calcium oxide particles 20 are pulverized to obtain calcium oxide particles 20 with adjusted particle size and shape.
[0069] The grinding step S30 is preferably a step of grinding the calcium oxide particles 20 until the average diameter of the calcium oxide particles 20 is 10 to 15 μm, since the calcium oxide particles 20 are easily uniformly dispersed in the resin composition obtained by mixing the calcium oxide powder, which is an aggregate of the calcium oxide particles 20, with a resin, and the calcium oxide particles 20 are easily exposed on the surface of the resin composition.
[0070] The grinding step S30 is preferably a step of grinding the calcium oxide particles 20 until the average diameter of the calcium oxide particles 20 is 1 to 3 μm, because when calcium oxide powder, which is an aggregate of the calcium oxide particles 20, is incorporated into fibers, the calcium oxide particles 20 are easily exposed on the surface of the fibers.
[0071] (effect) According to the method for producing an antibacterial agent of the present invention, it is possible to efficiently produce a sustained-release antibacterial agent whose antibacterial activity lasts for a long time.
[0072] Furthermore, in the method for producing an antibacterial agent according to the present invention, when eggshells are used as a raw material and the calcium oxide particles 20 constituting the antibacterial agent are baked eggshell particles, the calcium oxide particles 20 are formed from natural materials, so that an environmentally friendly antibacterial agent can be obtained.
[0073] The pulverization step S30 is performed, for example, by pulverizing the calcium oxide particles 20 using a known pulverizer. Note that a stone mill is shown in Fig. 10 as an example of the pulverization step S30. However, the pulverizer used in the pulverization step S30 of the present invention is not limited to the stone mill, and any known pulverizer can be used.
[0074] [Resin composition] The resin composition according to the present invention contains the antibacterial agent according to the present invention and a resin.
[0075] The resin is not particularly limited, but for example, crystalline resins and non-crystalline resins such as polypropylene, polypropylene copolymer, polyethylene, polystyrene, ABS resin, PVC resin, polycarbonate (PC) resin, polyamide (PA) resin such as nylon resin, polyurethane (PU) resin, polyacetal (POM) resin, elastomer resin, PBT resin, etc. can be used. Here, as the polypropylene, homo PP, random PP, block PP, etc. can be used. Furthermore, as the polypropylene copolymer, random polypropylene copolymer, block polypropylene copolymer, etc. can be used.
[0076] The resin may be a new resin that meets the standards and is provided on the market, but may also be a new OG (off-grade) resin; a recycled resin such as container packaging plastics, or a recycled resin.
[0077] As the recycled resin, for example, so-called "container recycling material" can be used. "Container recycling material" refers to recycled materials obtained by material recycling of plastic container and packaging waste collected by each city, town, and village based on the Volumetric Packaging Recycling Law. As the container recycling material, for example, PP container recycling material, PE container recycling material, etc. can be used. Here, PP container recycling material contains 90% by mass or more of polypropylene. Also, PE container recycling material contains 90% by mass or more of polyethylene. The shape of the container recycling material can be pellets, flakes, etc.
[0078] The resin composition according to the present invention is, for example, a raw material for the resin molded article according to the present invention described later. As described later, when the resin molded article according to the present invention has an antibacterial agent that is present in the resin and retains high antibacterial properties without contacting air or water, when the resin molded article is recycled, the antibacterial properties of the resin molded article after recycling can be easily maintained at a high level or increased. For this reason, the resin composition according to the present invention can be suitably used as a resin composition for material recycling using a resin that is new and within the standard and is provided on the market, a new OG (off-grade) resin, a regenerated resin such as a container packaging plastic, a recycled resin, etc. Here, the OG (off-grade) resin means a resin of an intermediate treatment grade that exists between a plurality of predetermined grades. An antibacterial agent may be appropriately added to the resin composition for material recycling.
[0079] The resin composition according to the present invention preferably has an antibacterial agent content of 1 to 20 mass %, since the antibacterial agent is easily uniformly dispersed in the resin composition and the antibacterial agent is easily increased on the surface of a resin molded article obtained by molding the resin composition.
[0080] The resin composition according to the present invention can be in the form of, for example, resin pellets.
[0081] (effect) According to the resin composition of the present invention, the surface and the inside of the resin composition and a resin molded article molded using the resin composition have antibacterial properties.
[0082] As described later, when the resin molded product according to the present invention contains an antibacterial agent that is present in the resin and does not come into contact with air or water, when the resin molded product is recycled, it has the effect that the antibacterial property of the recycled resin molded product can be easily maintained at a high level or can be easily increased. The resin molded product according to the present invention is suitable as a raw material for the resin molded product according to the present invention.
[0083] [Resin molding] A resin molded article can be produced by molding the resin composition according to the present invention. The resin molded article according to the present invention has the antibacterial agent according to the present invention present on the surface and inside of the resin. Examples of the resin molded article include a cup 1A(1), a tray 1B(1), a food tray 1C(1), and the like.
[0084] The resin molded article according to the present invention preferably contains an antibacterial agent in a content of 1 to 20% by mass, since the antibacterial agent is uniformly dispersed in the resin molded article, and the antibacterial agent is likely to be highly concentrated on the surface of the resin molded article.
[0085] The resin molded article according to the present invention can be formed, for example, by injection molding, extrusion molding, film extrusion molding, inflation molding, blow molding, press molding, or the like.
[0086] (effect) According to the resin molded article of the present invention, the surface and the inside of the resin molded article have antibacterial properties.
[0087] The antibacterial properties of the resin molded article according to the present invention are manifested by the surface of the antibacterial agent, which is mainly exposed to a space containing moisture or comes into contact with moisture, exhibiting a strong alkalinity of pH 12.0 or more. The reason why the surface of the antibacterial agent has a pH of 12.0 or more is that the exposed parts of calcium oxide contained in the calcium oxide particles 20 contained in the antibacterial agent react with moisture in the air or the like to generate calcium hydroxide, and this calcium hydroxide dissolves in moisture, causing the surface of the calcium oxide particles 20 to become strongly alkaline at a pH of 12.0 or more.
[0088] For example, when the resin molded product according to the present invention is a product of a dense resin having no internal voids and the antibacterial agent according to the present invention present on the surface and inside, the antibacterial properties of the resin molded product are mainly expressed on the surface of the antibacterial agent exposed on the surface of the resin molded product. Even when the resin molded product according to the present invention is a product of a dense resin having no internal voids and the antibacterial agent present on the surface and inside, cracks that reach the unexposed antibacterial agent may occur in the resin part, causing the antibacterial properties of the unexposed antibacterial agent to be expressed.
[0089] Furthermore, when the resin molding of the present invention is a sparse resin having internal voids or the like, and the antibacterial agent of the present invention is present on the surface and inside, the antibacterial properties of the resin molding are mainly expressed on the surface of the resin molding and on the surface of the antibacterial agent exposed to the internal voids.
[0090] On the other hand, among the antibacterial agents contained in the resin of the resin molded body according to the present invention, the antibacterial agents that are not exposed to a space containing moisture or that are not in contact with moisture do not produce calcium hydroxide and their composition does not change, since the calcium oxide contained in the calcium oxide particles 20 contained in the antibacterial agent does not react with moisture in the air, etc.
[0091] Therefore, among the antibacterial agents contained in the resin of the resin molded product according to the present invention, those that are not exposed to a space containing moisture or that are not in contact with moisture continue to retain their antibacterial function in the resin. Therefore, in the resin molded product according to the present invention, the antibacterial agent that is not exposed to a space containing moisture or that is not in contact with moisture among the antibacterial agents contained in the resin is likely to retain its antibacterial function when it is used again as a resin molded product in material recycling.
[0092] The following test was carried out to confirm whether the resin molded body according to the present invention can easily retain the function of the antibacterial agent when it is used again as a resin molded body in material recycling. First, a resin composition containing an antibacterial agent made of baked eggshell powder and a resin was molded into a resin molded body A according to the present invention, and the resin molded body A was used for one month. Next, the resin molded body A was crushed, and the resulting crushed material was used to mold the resin again to produce a resin molded body B. When the pH of the surfaces of these resin molded bodies A and B was measured, it was found that the pH of the surface of the resin molded body B was 12.0 or more, similar to the surface of the resin molded body A. In contrast, a resin molded body C was produced in the same manner as in the above test, except that scallop shell powder was used instead of the baked eggshell particles, and the resin molded body C was used for one month. Next, the resin molded body C was crushed, and the resulting crushed material was used to mold the resin again to produce a resin molded body D. When the pH of the surfaces of these resin molded bodies C and D was measured, it was found that the pH of the surface of the resin molded body C was 12.0 or more, but the pH of the surface of the resin molded body D was less than 12.0. Thus, it was found that the pH of the surface of a resin molded product using scallop shell powder after material recycling is likely to be less than 12.0, whereas the pH of the surface of a resin molded product according to the present invention using baked eggshell powder is likely to be 12.0 or higher after material recycling. In other words, it was found that the resin molded product according to the present invention using baked eggshell powder is likely to retain the antibacterial function when used again as a resin molded product through material recycling.
[0093] For example, consider a resin molded body in which, of all the antibacterial agents constituting the resin molded body according to the present invention, the proportion of the antibacterial agent exposed on the surface of the resin is 10% by mass, and the proportion of the antibacterial agent present in the resin and not in contact with air or water is 90% by mass. If this resin molded body is used for a sufficiently long period of time, the 10% by mass of the antibacterial agent exposed on the surface of the resin may lose its function as an antibacterial agent, but the 90% by mass of the antibacterial agent present in the resin is likely to continue to retain its function as an antibacterial agent. For this reason, even if a resin composition containing an antibacterial agent and a resin is prepared from a resin molded body that has been used for a sufficiently long period of time and this resin composition is used as is for material recycling, the resin molded body after recycling is likely to have 90% of the antibacterial property of the resin molded body before recycling. In addition, if a resin composition containing an antibacterial agent and a resin is prepared from a resin molded body that has been used for a sufficiently long period of time and a new antibacterial agent is added to this resin composition, it is also possible to make the resin molded body after recycling have an antibacterial property that is 100% or more of the antibacterial property of the resin molded body before recycling.
[0094] In this way, the resin molding of the present invention, which has an antibacterial agent that is present in the resin and does not come into contact with air or water, also has the effect that when material recycling is performed, the antibacterial properties of the recycled resin molding can be easily maintained at a high level or even increased.
[0095] [Antibacterial liquid] In the antibacterial agent according to the present invention, the pH of the particle surface of the calcium oxide particles 20 constituting the antibacterial agent is 12.0 or more. When the antibacterial agent is mixed with water, the resulting supernatant liquid 80 also becomes alkaline. The pH of this supernatant liquid 80 can be increased to 12.0 or more by increasing the mixing ratio of the antibacterial agent to the water. This supernatant liquid 80 with a pH of 12.0 or more can be used as the antibacterial liquid 80.
[0096] (effect) The antibacterial liquid according to the present invention can impart antibacterial properties to the surface of a target article by spraying or applying the liquid to the target article.
[0097] FIG. 11 is a diagram showing an example of the use of the antibacterial agent according to the present invention. As shown in FIG. 11, VOBLEED 20 (10), which is the antibacterial agent according to the present invention, can be used as the antibacterial agent 10 as it is. The antibacterial agent according to the present invention can be used as the supernatant liquid as the antibacterial liquid 80 by increasing the mixing ratio of the antibacterial agent to water. The antibacterial agent according to the present invention is mixed with a resin to obtain a resin composition 70 such as a resin pellet having an antibacterial surface. The resin composition 70 according to the present invention is molded to obtain a resin molded product 1 (1A, 1B, 1C) having an antibacterial surface. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0099] [Example 1] (Test piece) <Resin> A random polypropylene copolymer was prepared.
[0100] <Antibacterial agent> VOBLEED was prepared as an antibacterial agent. VOBLEED consisted of only baked eggshell powder. VOBLEED was classified to have a size within the range of 1 μm to 20 μm. "Size" refers to the maximum length of the particle. As shown in Test Example 1 below, when the baked eggshell powder that makes up VOBLEED was brought into contact with water, the pH of the supernatant of the mixture, which corresponds to the pH of the surface of the baked eggshell particles, was 12.34 after 1 minute and 12.50 after 3 minutes.
[0101] <Test Example 1> First, 500g of tap water was placed in a 1000ml beaker, and the pH and temperature of the water were measured, which was pH 7.56 and the water temperature 26.0°C. 1.5g of baked eggshell powder, which is an amount exceeding the saturated solubility of baked eggshell powder (VOBLEED) in tap water at 26.0°C (3 mass%), was added to this 500g of tap water, and stirred with a stirrer. The pH and temperature of the supernatant of the mixed liquid containing the undissolved baked eggshell powder were measured 0.5 minutes, 1 minute, 2 minutes, and 3 minutes after the addition of the baked eggshell powder. The measurements were performed three times, and the average pH and temperature were calculated. The results are shown in Table 1. In addition, 0.5 minutes after adding the baked eggshell powder, the mixture had a lot of undissolved powder and most of the powder was floating on the water surface. This is presumably due to the action of the water-repellent MgO contained in the baked eggshell powder.
[0102] <Test Example 2> Except for using calcium hydroxide powder (particle size 1 μm to 20 μm) instead of the baked eggshell powder, the pH and temperature of the water and the supernatant of the mixed liquid were measured in the same manner as in Test Example 1. The results are shown in Table 1.
[0103] <Test Example 3> Except for using calcium oxide powder (particle size 1 μm to 20 μm) instead of the baked eggshell powder, the pH and temperature of the water and the supernatant of the mixed liquid were measured in the same manner as in Test Example 1. The results are shown in Table 1.
[0104] As shown in Table 1, when calcium hydroxide powder (Test Example 2) and calcium oxide powder (Test Example 3) were mixed with water, the pH of the supernatant rose rapidly and reached equilibrium in 0.5 minutes. On the other hand, when baked eggshell powder (Test Example 1, VOBLEED) was mixed with water, the pH of the supernatant rose slowly and it took about 1 minute for the pH to reach equilibrium.
[0105] From Test Examples 1 to 3, it is believed that the baked eggshell powder (Test Example 1, VOBLEED) contains calcium oxide and magnesium oxide, which has a lower solubility, and therefore dissolves slower in water than calcium hydroxide powder and calcium oxide powder. On the other hand, the pH of the supernatant of the baked eggshell powder (Test Example 1, VOBLEED) exceeded pH 12.0 after 1 minute, and after 2 minutes it was equivalent to the pH of the supernatant of calcium hydroxide powder (Test Example 2) and calcium oxide powder (Test Example 3), demonstrating that the water in contact with the baked eggshell powder exhibits a sufficiently high alkalinity.
[0106] From these results, it is considered that the baked eggshell powder (Test Example 1, VOBLEED) has the function of causing water that it comes into contact with to exhibit a sufficiently high alkalinity, and that this property lasts for a longer period of time than calcium hydroxide powder or calcium oxide powder.
[0107] [Table 1]
[0108] <Preparation of test specimen> The random polypropylene copolymer and VOBLEED were kneaded to obtain pellets containing 98% by mass of the random polypropylene copolymer and 2% by mass of VOBLEED. A 50mm x 50mm test piece (test piece No. A2) was made from the above pellets. In test piece No. A2, each particle of VOBLEED was almost uniformly dispersed in the random polypropylene copolymer. Some of the VOBLEED was exposed on the surface of test piece No. A2.
[0109] (Test bacteria solution) Staphylococcus aureus (NBRC12732) and Escherichia coli (NBRC3972) were prepared as test bacteria. Using these test bacteria, test bacteria solutions were prepared in accordance with JIS Z 2801.
[0110] (Antibacterial Test) Using the above test pieces and test bacteria solution, antibacterial tests were carried out in accordance with JIS Z 2801. The test specimens were cleaned by exposing the surface of the specimen to ultraviolet UV light for 10 minutes. Two sterilized petri dishes were prepared, and one test piece was placed in each dish with the test surface facing up. 0.4 mL of the Staphylococcus aureus test bacteria solution was dropped onto the test surface of the test piece in one of the dishes, and 0.4 mL of the Escherichia coli test bacteria solution was dropped onto the test surface of the test piece in the other dish. The test bacteria liquid dropped onto each test piece was covered with a 40 mm x 40 mm PE film. After inoculation with the test bacteria liquid, the test specimens (sample No. SA2 (Staphylococcus aureus), sample No. EA2 (Escherichia coli)) were cultured for 24 hours at 35°C and a relative humidity of 90% or more, and the number of bacteria on the specimens was then measured to determine the antibacterial activity of the test specimens. The test conditions and results are shown in Table 2.
[0111] The number of bacteria in Table 2 is expressed in exponential form. For example, "1.4E+04" in Reference Example 1 is "1.4 x 10 4 " and "E+03" in Comparative Example 2 is "10 3 In Table 2, ND indicates "not detected."
[0112] The meanings of A, B, and C in the antibacterial activity assessment in Table 2 are as follows: A: The processed product (test piece containing an antibacterial agent) has an antibacterial effect compared to the unprocessed product (control test piece; test piece without an antibacterial agent) (the number of bacteria in the processed product is reduced by more than three orders of magnitude compared to the number of bacteria in the unprocessed product). B: The processed product is more likely to have an antibacterial effect than the unprocessed product (control test piece) (the number of bacteria in the processed product is two orders of magnitude lower than that of the unprocessed product). C: The processed product has no antibacterial effect compared to the unprocessed product (control test piece) (the number of bacteria in the processed product is reduced by one order of magnitude or less compared to the number of bacteria in the unprocessed product).
[0113] [Table 2]
[0114] [Reference Examples 1 and 2] (Control specimen) <Preparation of control specimen> The same PE film as that used in Example 1 was used as a control specimen (Specimen No. RA). Specimen No. RA was used in Reference Examples 1 and 2.
[0115] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a control test piece (test piece No. RA) was used instead of the test piece (test piece No. A2). In Reference Example 1, antibacterial tests were performed on control test pieces (Sample No. SRA0 (Staphylococcus aureus), Sample No. ERA0 (Escherichia coli)) immediately after inoculation with the test bacterial liquid (culture time 0). In Reference Example 2, antibacterial tests were performed on control test pieces (Sample No. SRA24 (Staphylococcus aureus), Sample No. ERA24 (Escherichia coli)) after inoculation with the test bacterial liquid and culture for 24 hours at 35°C and a relative humidity of 90% or more. The test conditions and results are shown in Table 2.
[0116] [Comparative Example 1] (Test piece) Using only the same random polypropylene copolymer as in Example 1, a test piece (test piece No. A1) of 50 mm×50 mm was prepared.
[0117] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. A1) was used instead of the test piece (test piece No. A2) (sample No. SA1 (Staphylococcus aureus), sample No. EA1 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0118] [Examples 2 to 4] (Test piece) <Preparation of test specimen> Test pieces (test piece Nos. A3 to A5) were prepared in the same manner as in Example 1, except that the compounding ratio of the random polypropylene copolymer and the VOBLEED was changed as shown in Table 2. In the test piece Nos. A3 to A5, each particle of the VOBLEED was contained in the random polypropylene copolymer in a nearly uniformly dispersed state. A part of the VOBLEED was exposed on the surface of the test piece Nos. A3 to A5.
[0119] (Surface analysis of test pieces) The surface of test piece No. A3 was observed using scanning electron microscope (SEM) photographs and qualitatively analyzed using scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX).
[0120] FIG. 12 is an example of a scanning electron microscope (SEM) photograph of the surface of resin molded body 1D(1) made of test piece No. A3 of Example 2, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). FIG. 13 is an example of a qualitative analysis result of FIG. 12, shown only in terms of Ca distribution. In the figure, the relatively white parts are parts shown only in terms of Ca distribution. FIG. 14 is an example of a qualitative analysis result of FIG. 12, shown only in terms of Mg distribution. In the figure, the relatively white parts are parts shown only in terms of Mg distribution. FIG. 15 is an example of a qualitative analysis result of FIG. 12, shown only in terms of O distribution. In the figure, the relatively white parts are parts shown only in terms of O distribution.
[0121] FIG. 16 is an example of a scanning electron microscope (SEM) photograph of another surface of resin molded body 1D made of test piece No. A3 of Example 2, taken by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX). FIG. 17 is an example of a qualitative analysis result of FIG. 16, shown only in terms of Ca distribution. In the figure, the relatively white parts are parts shown only in terms of Ca distribution. FIG. 18 is an example of a qualitative analysis result of FIG. 16, shown only in terms of Mg distribution. In the figure, the relatively white parts are parts shown only in terms of Mg distribution. FIG. 19 is an example of a qualitative analysis result of FIG. 16, shown only in terms of O distribution. In the figure, the relatively white parts are parts shown only in terms of O distribution.
[0122] According to FIG. 12, in the resin molding 1D consisting of test piece No. A3, it was found that calcium oxide particles (burnt eggshell powder, VOBLEED) 20 (20Aa, 20Ab, 20Ac, etc.) having a diameter of about 20 μm are exposed on the surface of the resin 50 consisting of a random polypropylene copolymer.
[0123] 13 and 14, all of the calcium oxide particles 20Aa, 20Ab, and 20Ac contain Ca and Mg. Also, FIG. 15 shows that all of the calcium oxide particles 20Aa, 20Ab, and 20Ac contain O.
[0124] 12 to 14, it was found that all of the calcium oxide particles 20Aa, 20Ab, and 20Ac contain Ca and Mg. Also, according to Fig. 15, it is presumed that the calcium oxide particles 20Aa, 20Ab, and 20Ac contain an oxide of Ca and an oxide of Mg, but in consideration of the results of Test Example 1, it can be said that the calcium oxide particle 20 contains calcium oxide and magnesium oxide for the following reasons.
[0125] That is, the result that the dissolution rate of the burned eggshell powder (Test Example 1, VOBLEED) in water in Test Example 1 is lower than that of the calcium oxide powder (Test Example 3) indicates that the calcium oxide particles (burned eggshell powder, VOBLEED) 20 contain magnesium oxide, which is a substance that is less soluble in water than calcium oxide. That is, the calcium oxide particles (burned eggshell powder, VOBLEED) 20 contain calcium oxide and magnesium oxide.
[0126] Also, according to Figure 16, in the resin molding 1D consisting of test piece No. A3, calcium oxide particles (burned eggshell powder, VOBLEED) 20Ba having a size of approximately 20 μm, calcium oxide particles (burned eggshell powder, VOBLEED) 20Bb, 20Bc, 20Bd, and 20Be having a size of approximately 5 to 8 μm, and calcium oxide particles (burned eggshell powder, VOBLEED) 20Bf and 20Bg having a size of 1 μm or more and less than 5 μm are exposed on the surface of the resin 50 consisting of a random polypropylene copolymer.
[0127] On the other hand, it was found from Figures 17 and 18 that all of the calcium oxide particles 20Ba, 20Bb, 20Bc, 20Bd, 20Be, 20Bf, and 20Bg contain Ca and Mg, and from Figure 19 that all of the calcium oxide particles 20Ba, 20Bb, 20Bc, 20Bd, 20Be, 20Bf, and 20Bg contain O.
[0128] 16 to 18, it was found that all of the calcium oxide particles 20Ba, 20Bb, 20Bc, 20Bd, 20Be, 20Bf, and 20Bg having a size of 1 μm or more and 20 μm or less contain Ca and Mg. Also, according to Fig. 19, it is presumed that the calcium oxide particles 20Ba, 20Bb, 20Bc, 20Bd, 20Be, 20Bf, and 20Bg contain Ca oxide and Mg oxide, but for the above reasons in consideration of the results of Test Example 1, it can be said that the calcium oxide particle 20 contains calcium oxide and magnesium oxide.
[0129] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test pieces (test piece No. A3 to A5) were used instead of the test piece (test piece No. A2) (sample No. SA3 to SA5 (Staphylococcus aureus), sample No. EA3 to EA5 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0130] From the results of Example 2, it can be said that in the resin molding 1D, the calcium oxide particles (baked eggshell powder, VOBLEED) 20 present on the surface of the resin 50 made of a random polypropylene copolymer have a size in the range of 1 μm or more and 20 μm or less, and the calcium oxide particles 20 contain calcium oxide and magnesium oxide, and as a result, it is considered that the results of the antibacterial test were good.
[0131] [Reference Examples 3 and 4] (Control specimen) A test specimen (test specimen No. RB) was prepared by subjecting the same test specimen as the control test specimen (test specimen No. RA) of Reference Examples 1 and 2 to a water-resistant treatment. Test specimen No. RB was used in Reference Examples 3 and 4. The water resistance treatment was performed by immersing the sample in 50° C. water for 16 hours, which is the immersion condition for SIAA water resistance category 2.
[0132] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a control test piece (test piece No. RB) was used instead of the test piece (test piece No. A2). In Reference Example 3, antibacterial tests were performed on control test pieces (Sample No. SRB0 (Staphylococcus aureus), Sample No. ERB0 (Escherichia coli)) immediately after inoculation with the test bacterial liquid (culture time 0). In Reference Example 4, antibacterial tests were performed on control test pieces (Sample No. SRB24 (Staphylococcus aureus), Sample No. ERB24 (Escherichia coli)) after inoculation with the test bacterial liquid and culture for 24 hours at 35°C and a relative humidity of 90% or more. The test conditions and results are shown in Table 2.
[0133] [Comparative Example 2] (Test piece) The same test piece as the test piece in Comparative Example 1 (Test Piece No. A1) was subjected to a water-resistant treatment to prepare a test piece in Comparative Example 2 (Test Piece No. B1). The water resistance treatment was performed by immersing the sample in 50° C. water for 16 hours, which is the immersion condition for SIAA water resistance category 2.
[0134] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. B1) was used instead of the test piece (test piece No. A2) (sample No. SB1 (Staphylococcus aureus), sample No. EB1 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0135] [Examples 5 to 8] (Test piece) Test pieces identical to those of Examples 1 to 4 (test piece Nos. A2 to A5) were each subjected to a water-resistant treatment to prepare test pieces of Examples 5 to 8 (test piece Nos. B2 to B5). The water resistance treatment was performed by immersing the sample in 50° C. water for 16 hours, which is the immersion condition for SIAA water resistance category 2.
[0136] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test specimens (test specimen Nos. B2 to B5) were used instead of test specimen No. A2 (sample Nos. SB2 to SB5 (Staphylococcus aureus), sample Nos. EB2 to EB5 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0137] [Example 9] (Test piece) <Resin> Polystyrene was prepared.
[0138] <Antibacterial agent> The same VOBLEED as in Example 1 was prepared.
[0139] <Preparation of test specimen> The polystyrene and vobleed were mixed to obtain pellets containing 98% by mass of polystyrene and 2% by mass of vobleed. A 50mm x 50mm test piece (test piece No. C2) was made from the above pellets. In test piece No. C2, each particle of VOBLEED was almost uniformly dispersed in the polystyrene. Some of the VOBLEED was exposed on the surface of test piece No. C2.
[0140] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. C2) was used instead of the test piece (test piece No. A2) (sample No. SC2 (Staphylococcus aureus), sample No. EC2 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0141] [Reference Examples 5 and 6] (Control specimen) <Preparation of control specimen> The same PE film as that used in Example 1 was used as a control specimen (specimen No. RC).
[0142] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a control test piece (test piece No. RC) was used instead of the test piece (test piece No. A2). In Reference Example 5, an antibacterial test was performed on the control test pieces (Sample No. SRC0 (Staphylococcus aureus), Sample No. ERC0 (Escherichia coli)) immediately after inoculation with the test bacterial liquid (culture time 0). In Reference Example 6, an antibacterial test was performed on the control test pieces (Sample No. SRC24 (Staphylococcus aureus), Sample No. ERC24 (Escherichia coli)) after inoculation with the test bacterial liquid and culture for 24 hours at 35°C and a relative humidity of 90% or more. The test conditions and results are shown in Table 2.
[0143] [Comparative Example 3] (Test piece) A 50 mm×50 mm test piece (test piece No. C1) was prepared using only the same polystyrene as in Example 9.
[0144] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. C1) was used instead of the test piece (test piece No. A2) (sample No. SC1 (Staphylococcus aureus), sample No. EC1 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0145] [Examples 10 to 12] (Test piece) <Preparation of test specimen> Test pieces (test pieces No. C3 to C5) were prepared in the same manner as in Example 9, except that the compounding ratio of the polystyrene and VOBLEED was changed as shown in Table 2. In test pieces No. C3 to C5, each particle of VOBLEED was contained in the polystyrene almost uniformly dispersed state. A part of VOBLEED was exposed on the surface of test pieces No. C3 to C5.
[0146] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test specimens (test specimen Nos. C3 to C5) were used instead of the test specimen (test specimen No. A2) (sample Nos. SC3 to SC5 (Staphylococcus aureus), sample Nos. EC3 to EC5 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0147] [Example 13] (Test piece) <Resin> ABS resin was prepared.
[0148] <Antibacterial agent> The same VOBLEED as in Example 1 was prepared.
[0149] <Preparation of test specimen> The ABS resin and the vobleed were mixed to obtain pellets containing 98% by mass of ABS resin and 2% by mass of vobleed. A 50mm x 50mm test piece (test piece No. D2) was made from the above pellets. In test piece No. D2, each particle of VOBLEED was almost uniformly dispersed in the ABS resin. Some of the VOBLEED was exposed on the surface of test piece No. D2.
[0150] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. D2) was used instead of the test piece (test piece No. A2) (sample No. SD2 (Staphylococcus aureus), sample No. ED2 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0151] [Reference Examples 7 and 8] (Control specimen) <Preparation of control specimen> The same PE film as that used in Example 1 was used as a control specimen (Specimen No. SRD).
[0152] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a control test specimen (test specimen No. SRD) was used instead of the test specimen (test specimen No. A2). In Reference Example 7, an antibacterial test was performed on the control test pieces (Sample No. SRD0 (Staphylococcus aureus), Sample No. ERD0 (Escherichia coli)) immediately after inoculation with the test bacterial liquid (culture time 0). In Reference Example 8, an antibacterial test was performed on the control test pieces (Sample No. SRD24 (Staphylococcus aureus), Sample No. ERD24 (Escherichia coli)) after inoculation with the test bacterial liquid and culture for 24 hours at 35°C and a relative humidity of 90% or more. The test conditions and results are shown in Table 2.
[0153] [Comparative Example 4] (Test piece) A test piece (test piece No. D1) of 50 mm×50 mm was prepared using only the same ABS resin as in Example 13.
[0154] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. D1) was used instead of the test piece (test piece No. A2) (sample No. SD1 (Staphylococcus aureus), sample No. ED1 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0155] [Examples 14 to 16] (Test piece) <Preparation of test specimen> Test pieces (test piece Nos. D3 to D5) were prepared in the same manner as in Example 13, except that the compounding ratio of the ABS resin and the VOBLEED was changed as shown in Table 2. In test piece Nos. D3 to D5, each particle of the VOBLEED was contained in the ABS resin and dispersed almost uniformly. Some of the VOBLEED was exposed on the surface of test piece Nos. D3 to D5.
[0156] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test pieces (test piece No. D3 to D5) were used instead of the test piece (test piece No. A2) (sample No. SD3 to SD5 (Staphylococcus aureus), sample No. ED3 to ED5 (Escherichia coli)). The test conditions and results are shown in Table 2.
[0157] [Example 17] (Test piece) <Resin> PP container recycling pellets were prepared. Here, "PP container recycling pellets" refers to pellets of container recycling material made of PP (polypropylene). Also, "container recycling material" refers to recycled materials obtained by material recycling of plastic container and packaging waste collected by each city, town, and village based on the Volumetric Packaging Recycling Law. The PP container recycling pellets contain 90% or more by mass of PP, with the remainder consisting of resins other than PP and other impurities.
[0158] <Antibacterial agent> The same VOBLEED as in Example 1 was prepared.
[0159] <Preparation of test specimen> The PP container recycling pellets were mixed with vobleed to obtain pellets containing 99% by mass of PP container recycling material and 1% by mass of vobleed. A 50mm x 50mm test piece (test piece E2) was made from the above pellets. In test piece E2, each particle of VOBLEED was almost uniformly dispersed in the PP container material. Some of the VOBLEED was exposed on the surface of test piece E2.
[0160] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. E2) was used instead of the test piece (test piece No. A2) (sample No. SE2 (Staphylococcus aureus), sample No. EE2 (Escherichia coli)). The test conditions and results are shown in Table 3.
[0161] [Table 3]
[0162] [Reference example 9] (Control specimen) <Preparation of control specimen> The same PE film as that used in Example 1 was used as a control specimen (specimen No. RE).
[0163] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a control test piece (test piece No. RE) was used instead of the test piece (test piece No. A2). An antibacterial test was conducted on the control test pieces (sample No. SRE0 (Staphylococcus aureus), sample No. ERE0 (Escherichia coli)) immediately after inoculation with the test bacteria solution (incubation time 0). The test conditions and results are shown in Table 3. The meaning of antibacterial activity judgment (A) in Table 3 is the same as that of antibacterial activity judgment (A) in Table 2.
[0164] [Comparative Example 3] (Test piece) Using only the same PP container recycling pellets as in Example 17, a 50 mm x 50 mm test piece (test piece No. E1) made of 100 mass % PP container recycling material was prepared.
[0165] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. E1) was used instead of the test piece (test piece No. A2) (sample No. SE1 (Staphylococcus aureus), sample No. EE1 (Escherichia coli)). The test conditions and results are shown in Table 3.
[0166] [Examples 18 to 20] (Test piece) <Preparation of test specimen> Test pieces (test pieces No. E3 to E5) were prepared in the same manner as in Example 17, except that the compounding ratio of the PP container refill pellets and the VOBLEED was changed as shown in Table 3. In test pieces No. E3 to E5, each particle of the VOBLEED was contained almost uniformly dispersed in the PP container refill material. Some of the VOBLEED was exposed on the surface of test pieces No. E3 to E5.
[0167] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test specimens (test specimen Nos. E3 to E5) were used instead of the test specimen (test specimen No. A2) (sample Nos. SE3 to SE5 (Staphylococcus aureus), sample Nos. EE3 to EE5 (Escherichia coli)). The test conditions and results are shown in Table 3.
[0168] [Reference example 10] (Test piece) <Resin> The same PP repellets as in Example 17 were prepared.
[0169] <Antibacterial agent> As an antibacterial agent, Zeomic LJ10D-CP (D), a low-discoloration resin-added antibacterial agent manufactured by Sinanen Zeomic Co., Ltd., was used. 50 : 7-10 μm, average particle size: 8-12 μm) were prepared. Zeomic LJ10D-CP was made up of particles that encapsulated a silver-based inorganic antibacterial agent with silver ions supported in a zeolite framework.
[0170] <Preparation of test specimen> The PP refill pellets and Zeomic LJ10D-CP were mixed together to obtain pellets containing 99.7% by mass of PP refill pellets and 0.3% by mass of Zeomic LJ10D-CP. A 50mm x 50mm test piece (test piece E6) was made from the above pellets. In test piece E6, the Zeomic LJ10D-CP particles were dispersed almost uniformly in the PP container material. Some Zeomic LJ10D-CP was exposed on the surface of test piece E6.
[0171] (Antibacterial Test) An antibacterial test was carried out in the same manner as in Example 1, except that a test piece (test piece No. E6) was used instead of the test piece (test piece No. A2) (sample No. SE6 (Staphylococcus aureus), sample No. EE6 (Escherichia coli)). The test conditions and results are shown in Table 3.
[0172] [Reference Examples 11 and 12] (Test piece) <Preparation of test specimen> Test pieces (test piece No. E7 (Reference Example 11) and E8 (Reference Example 12)) were prepared in the same manner as in Reference Example 10, except that the compounding ratio of the above PP container recycling pellets and Zeomic LJ10D-CP was changed as shown in Table 3. In test pieces No. E7 and E8, the particles of Zeomic LJ10D-CP were contained almost uniformly dispersed in the PP container recycling material. Some VOBLEED was exposed on the surface of test pieces No. E7 and E8.
[0173] (Antibacterial Test) Antibacterial tests were conducted in the same manner as in Example 1, except that test pieces (test piece No. E7 and E8) were used instead of the test piece (test piece No. A2) (sample No. SE7 and SE8 (Staphylococcus aureus), sample No. EE7 and EE8 (Escherichia coli)). The test conditions and results are shown in Table 3.
[0174] From Tables 2 and 3, it is clear that the antibacterial agent on the surface of the resin molded article is high when the VOBLEED content of the resin molded article is in the range of 1 to 20 mass %.
[0175] The present invention is not limited to the above-described embodiment, and can be modified as appropriate. [Explanation of symbols]
[0176] 1, 1A, 1B, 1C, 1D Resin molding 10 Antibacterial agents 20, 20Aa, 20Ab, 20Ac, 20Ba, 20Bb, 20Bc, 20Bd, 20Be, 20Bf, 20Bg Calcium oxide particles (calcined eggshell, calcined eggshell particles) 50 Resin 70 Resin composition (resin pellets) 80 Supernatant liquid (antibacterial liquid) 100, 100A, 100B, 100C, 100D, 100E Dried eggshell S20 Firing process S30 Crushing process
Claims
1. The present invention includes calcium oxide particles containing calcium oxide and a hydration-inhibiting component that inhibits hydration of the calcium oxide, The antibacterial agent has a surface pH of the calcium oxide particles of 12.0 or higher.
2. 2. The antibacterial agent according to claim 1, wherein the hydration-inhibiting component is magnesium oxide.
3. 3. The antibacterial agent according to claim 2, wherein the calcium oxide particles have a dispersed phase made of magnesium oxide dispersed in a matrix phase made of calcium oxide.
4. 3. The antibacterial agent according to claim 1, wherein the calcium oxide particles are baked eggshell particles.
5. The antibacterial agent according to any one of claims 1 to 3, A resin composition comprising:
6. A resin molded article comprising the resin composition according to claim 5 .
7. A method for producing an antibacterial agent comprising a calcination step of calcining dried eggshells at 1000°C or higher for 1 to 2 hours to obtain calcium oxide particles containing calcium oxide and a hydration-inhibiting component that inhibits hydration of the calcium oxide, the calcium oxide particles having a surface pH of 12.0 or higher.
Citation Information
Patent Citations
Antimicrobial treatment material for water treatment and water treatment method
JP2013056833A
Manufacturing method of resin composition
JP2017114953A
High-purity calcium oxide compound
JP2018501180A
Eggshell powder-containing resin composition, and eggshell powder-containing resin molding
JP2023165221A
Multifunctional powder IMCREE and its manufacturing method
JP2023532466A